One-year incidence of venous thromboembolism, bleeding, and death in patients with solid tumors newly initiating cancer treatment: Results from the Cancer-VTE Registry. Issue 213 (May 2022) - Ohashi, Yasuo; Ikeda, Masataka; Kunitoh, Hideo; Sasako, Mitsuru; Okusaka, Takuji; Mukai, Hirofumi; Fujiwara, Keiichi; Nakamura, Mashio; Oba, Mari S.; Kimura, Tetsuya; Ibusuki, Kei; Takita, Atsushi; et al.
Abstract: Introduction: Although many publications have reported the incidence of venous thromboembolism (VTE) in patients with cancer from Western countries, to date, no prospective East Asian studies have been published, and potential racial differences remain unclear. The multicenter, prospective, observational Cancer-VTE Registry aimed to clarify the incidence of VTE and bleeding and identify risk factors in Japanese patients with solid tumors after one year of follow-up. Materials and methods: Patients with colorectal, lung, stomach, pancreatic, breast, or gynecologic cancer were enrolled after VTE screening and before starting cancer treatment. The follow-up period was one year. The main outcomes were the incidences of symptomatic VTE, bleeding events (major or clinically relevant non-major), and all-cause death, evaluated according to VTE presence/absence at baseline. Multivariate analyses were conducted to identify risk factors for events. Results: Among 9630 patients, the one-year cumulative incidences of symptomatic VTE, bleeding events, and all-cause death were 0.5%, 1.4%, and 12.2%, respectively. The majority of VTEs identified at baseline were asymptomatic distal deep vein thromboses; however, affected patients had higher event rates during the follow-up period. The most important independent risk factor for developing symptomatic VTE, bleeding events, and death during the follow-up period was the presence of symptomatic or asymptomatic VTE at baseline. Conclusions: These data have revealed the incidence of symptomatic VTE in Japanese patients with solid tumors during one year of follow-up. The presence of any VTE before initiating cancer treatment was an independent risk factor for symptomatic VTE, bleeding events, and death during subsequent treatment.